Indonesian Language as a Lingua Franca in English Class at Community Learning Center (CLC) Pontian Fico, Sabah-Malaysia - Aswan (ELITE Association Indonesia, 2023)
The purpose of this study is to explore and describe the use of the Indonesian language as the lingua franca in learning English at the Pontian Fico Community Learning Center, Sabah-Malaysia. The Community Learning Center (CLC) is the center for Indonesian learning activities in Sabah-Malaysia. Students who join the CLC are Indonesian citizens. The type of method used in this study is qualitative with data collection using interview techniques. The data analysis techniques are collecting data, reducing data, analyzing data, and verifying data. The results of this study indicate that the teacher uses Indonesian as a lingua franca by considering two things, namely the teacher's background and the student's background. The use of Indonesian as a lingua franca has advantages, among others, teachers and students can communicate in two directions. However, among these uses tend to display code mixing to explain the pronunciation of vocabulary. The conclusion drawn from this research is that the use of Indonesian as a lingua franca in learning English at CLC Pontian Fico is the right step. Keywords: Indonesian language, lingua franca, english class